C01 Add Maths Answers Form 4 PDF
C01 Add Maths Answers Form 4 PDF
C01 Add Maths Answers Form 4 PDF
2.
(a) (b) (c) y
y y
Vertical Vertical
Vertical line test line test
line test 1
x x x
0 0 0 2
Function because the Not a function because Function because the vertical
vertical line test cuts only the vertical line test cuts line test cuts only one point
1 point on the graph. more than 1 point on the on the graph except at x = 2
graph. where it does not cut any
point.
90 100
240
Total price (RM)
house (km)
Eaten calories
72 180
54
120
36
18 60
0 x 0 x 0 x
1 2 3 4 5 1 2 3 4 10 20
Number of tickets Number of packets of popcorn Time (seconds)
1
2. (a) The graph for Situation I is a discrete graph while the graph for Situation II and
Situation III is a continuous graph.
(b)
Situation I Situation II Situation III
Domain {1, 2, 3, 4, 5} 1<x<4 0 < x < 20
Range {18, 36, 54, 72, 90} 60 < y < 240 0 < y < 100
f(x)
f(x) = |x + 1|
5
1
x
–2 –1 0 4
f(x)
8
f(x) = |4 – 2x|
4
x
–2 0 2 4
2
(c)
x –2 –1 0 1 2 3 4
f(x) = 2x – 5 9 7 5 3 1 1 3
(x, y) (–2, 9) (–1, 7) (0, 5) (1, 3) (2, 1) (3, 1) (4, 3)
f(x)
9
5
f(x)=|2x – 5|
3
x
–2 0 5– 4
2
Thus, range of f is 0 < f(x) < 9.
( )
g 1 =3+
2
6
1 –1
2
= –9
(b) g(b) = 2b
3 + 6 = 2b
b–1
3(b – 1) + 6 = 2b(b – 1)
3b – 3 + 6 = 2b2 – 2b
2b2 – 5b – 3 = 0
(2b + 1)(b – 3) = 0
2b + 1 = 0 or b – 3 = 0
b = – 1 or b=3
2
Thus, the possible values for b are – 1 and 3.
2
3
2. (a) h(x) = kx – 3
x–1
h(2) = 5
2k – 3 = 5
2–1
2k – 3 = 5
2k = 8
k=4
(b) h(x) = kx – 3
x–1
h(3) = k
3k – 3 = k
3–1
3k – 3 = 2k
k=3
(c) h(x) = kx – 3
x–1
h(k) = k
k – 3 = k
2
k–1
k2 – 3 = k2 – k
k=3
3. (a) f(x) = 4x – 3
f(–2) = 4(–2) – 3
= –8 – 3
= –11
= 11
( )1
2 ( )
f – = 4 – 1 – 3
2
= –2 – 3
= –5
=5
(b) f(x) = 1
4x – 3 = 1
4x – 3 = –1 or 4x – 3 = 1
4x = 2 or 4x = 4
x= 2 or x=1
4
= 1
2
(c) f(x) , 1
4x – 3 , 1
–1 , 4x – 3 , 1
2 , 4x , 4
1 , x , 1
2
4
(d) f(x) . 5
4x – 3 . 5
4x – 3 , –5 4x – 3 . 5
4x , –2 4x . 8
x , – 1 or x . 2
2
4. g(x) = 6 – 2x
g(x) = x
6 – 2x = x
6 – 2x = –x or 6 – 2x = x
3x = 6
x=2
5. (a) f(x) = mx + c
f(2) = 7
2m + c = 7…1
f(4) = –1
4m + c = –1…2
2 – 1: 2m = –8
m = –4
Substitute m = – 4 into 1: 2(– 4) + c = 7
–8 + c = 7
c = 15
Thus, m = – 4 and c = 15.
(b) f(x) = – 4x + 15 (c) f(x) = x
f(2) = –4(2) + 15 – 4x + 15 = x
= –8 + 15 5x = 15
= 7 x = 3
This graph is not a function This graph is not a function The graph is a function
because the vertical line test because the vertical line test because the vertical line test
cuts three points on the cuts two points on the only cuts one point on the
graph. graph. graph except on the line
x = 2.
5
3. (a) This relation is a function because each object has only one image.
(b) Domain = {–7, –6, 6, 7}
Range = {36, 49}
(c) f : x ˜ x2
= 81 – 1
= 80 metres
(ii) H(1) = 81 – 9(1)2
= 81 – 9
= 72 metres
(iii) H(2) = 81 – 9(2)2
= 81 – 36
= 45 metres
(b) The stone reaches the ground when H(t) = 0
H(t) = 0
81 – 9t2 = 0
9t2 – 81 = 0
(3t – 9)(3t + 9) = 0
3t – 9 = 0 or 3t + 9 = 0
3t = 9 3t = –9
t = 3 t = –3 (Ignore)
Thus, the stone reaches the ground when t = 3 seconds.
Inquiry 2 (Page 12)
5. The function f [g(x)] is obtained by substituting function g into the function f.
f(x) = x + 2
f [g(x)] = f(x2)
= x2 + 2
6. The graph of f [g(x)] is a parabola that has a minimum point.
6
9. The graph of g[f(x)] is obtained by substituting function f into the function g.
g(x) = x2
g[f(x)] = g(x + 2)
= (x + 2)2
= x2 + 4x + 4
10. The graph of g[f(x)] is a parabola that has a minimum point.
Mind Challenge (Page 14)
g[f(x)] = g(x)
= x2 = x2
Thus, the function fg and gf are not necessarily always different.
Self Practice 1.4 (Page 14)
1. (a) f(x) = 3x
(b) gf(x) = 2x – 7
2. (a) f(x) = 3x, g(x) = 3 – x
fg(x) = f(3 – x)
= 3(3 – x)
= 9 – 3x
fg: x ˜ 9 – 3x
gf(x) = g(3x)
= 3 – 3x
gf: x ˜ 3 – 3x
f 2 = ff(x)
= f(3x)
= 3(3x)
= 9x
f 2: x ˜ 9x
g2 = gg(x)
= g(3 – x)
= 3 – (3 – x)
= x
g2: x ˜ x
(b) f(x) = 4 + 2x, g(x) = x2
fg(x) = f(x2)
= 4 + 2(x2)
= 4 + 2x2
fg: x ˜ 4 + 2x2
gf(x) = g(4 + 2x)
= (4 + 2x)2
= 16 + 16x + 4x2
= 4x2 + 16x + 16
gf: x ˜ 4x2 + 16x + 16
7
f 2 = ff(x)
= f(4 + 2x)
= 4 + 2(4 + 2x)
= 4 + 8 + 4x
= 4x + 12
f 2: x ˜ 4x + 12
g2(x) = gg(x)
= g(x2)
= (x2)2
= x4
g2: x ˜ x4
(c) f(x) = x + 4, g(x) = 6 , x ≠ 0
x
( )
fg(x) = f 6
x
= 6 + 4, x ≠ 0
x
fg: x ˜ 6 + 4, x ≠ 0
x
gf(x) = g(x + 4)
= 6 , x ≠ – 4
x+4
gf: x ˜ 6 , x ≠ – 4
x+4
f 2 = ff(x)
= f(x + 4)
= x+4+4
= x+8
f : x ˜ x + 8
2
g2 = gg(x)
( )
= g 6
x
= 6
6
x
= x
g2: x ˜ x
(d) f(x) = x – 5, g(x) = 1 , x ≠ 1
x–1
(
fg(x) = f 1 )
x–1
= 1 –5
x–1
= 1 – 5x + 5
x–1
= 6 – 5x , x ≠ 1
x–1
fg: x ˜ 6 – 5x , x ≠ 1
x–1
8
gf(x) = g(x – 5)
= 1
x–5–1
= 1 ,x≠6
x–6
gf: x ˜ 1 , x ≠ 6
x–6
f 2 = ff(x)
= f(x – 5)
= x–5–5
= x – 10
f : x ˜ x – 10
2
g2 = gg(x)
(
= g 1 )
x–1
= 1
1 –1
x–1
= 1
1–x+1
x–1
= x–1,x≠2
2–x
g : x ˜ x – 1 , x ≠ 2
2
2–x
3. f(x) = 3x + 4, g(x) = x2 + 6
fg(x) = f(x2 + 6)
= 3(x2 + 6) + 4
= 3x2 + 18 + 4
= 3x2 + 22
gf(x) = g(3x + 4)
= (3x + 4)2 + 6
= 9x2 + 24x + 16 + 6
= 9x2 + 24x + 22
(a) f=g
3x + 4 = x2 + 6
x – 3x + 2 = 0
2
(x – 1)(x – 2) = 0
x–1=0 or x–2=0
x=1 or x=2
(b) fg = gf
3x2 + 22 = 9x2 + 24x + 22
6x2 + 24x = 0
6x(x + 4) = 0
6x = 0 or x + 4 = 0
x= –4
9
4. Given f(x) = ax + b, f 2(x) = 4x – 9
f 2(x) = ff(x)
4x – 9 = f(ax + b)
4x – 9 = a(ax + b) + b
4x – 9 = a2x + ab + b
Equate the coefficients:
a2 = 4
a = ±!w 4
= –2 or 2
When a = –2, –2b + b = –9
b=9
When a = 2, 2b + b = –9
3b = –9
b = –3
Thus, a = –2, b = 9 or a = 2, b = –3.
5. f(x) = 3x + k, g(x) = 2h – 3x
fg = gf
f(2h – 3x) = g(3x + k)
3(2h – 3x) + k = 2h – 3(3x + k)
6h – 9x + k = 2h – 9x – 3k
4h = –4k
h = –k
Self Practice 1.5 (Page 15)
1. (a) f(x) = 2x + 1, g(x) = x , x ≠ 1
x–1
(
fg(x) = f x )
x–1
(
=2 x
x–1) +1
= 2x + x –1
x–1
= 3x – 1, x ≠ 1
x–1
3(3) – 1
fg(3) =
3–1
= 8
2
=4
(b) f(x) = 5x + 6, g(x) = 2x – 1
gf(x) = g(5x + 6)
= 2(5x + 6) – 1
= 10x + 12 – 1
= 10x + 11
( ) 1
5 ( )
gf – = 10 – 1 + 11
5
= –2 + 11
=9
10
(c) f(x) = x + 1 , x ≠ 3, g(x) = 6 , x ≠ 2
x–3 x–2
(
f (x) = f
2 x
)
x–3
+ 1
x+1 +1
= x–3
x+1 –3
x–3
= x + 1 + x – 3 ÷ x + 1 – 3x + 9
x–3 x–3
= 2x – 2 × x – 3
x–3 10 – 2x
= 2x – 2
10 – 2x
= x–1,x≠5
5–x
4–1
f 2(4) =
5–4
=3
(
g2(x) = g 6 )
x–2
= 6
6 –2
x–2
= 6 ÷ 6 – 2x + 4
x–2
= 6 × x –2
10 – 2x
= 6x – 12
10 – 2x
= 3x – 6, x ≠ 5
5–x
( )3 1 –6
g ( )
2 1
= 2
2
( )
5– 1
2
= –9 ÷ 9
2 2
= –1
(d) f(x) = x2 – 4, g(x) = 2 , x ≠ 2
x–2
f 2(x) = f(x2 – 4)
= (x2 – 4)2 – 4
= x4 – 8x2 + 16 – 4
= x4 – 8x2 + 12
f (–1) = (–1)4 – 8(–1)2 + 12
2
= 1 – 8 + 12
=5
11
g2(x) = g ( x –2 2 )
= 2
2 –2
x–2
= 2 ÷ 2 – 2x + 4
x–2
= 2 × x – 2
6 – 2x
= x – 2 , x ≠ 3
3–x
g (1) = – 2
2 1
3–1
= – 1
2
2. (a) f(x) = 2x – 5, g(x) = 10 , x ≠ 0
x
fg(x) = 5
( ) f 10 = 5
x
( )
2 10
x
–5=5
20 – 5x = 5x
10x = 20
x = 2
(b) f(x) = x2 – 1, g(x) = 2x + 1
gf(x) = 7
g(x2 – 1) = 7
2(x2 – 1) + 1 = 7
2x2 – 2 + 1 = 7
2x2 = 8
x2 = 4
x = ±!w4
x = –2, x = 2
(c) f(x) = 3x – 2, f 2(x) = 10
f 2(x) = 10
f(3x – 2) = 10
3(3x – 2) – 2 = 10
9x – 6 – 2 = 10
9x = 18
x=2
12
(d) g(x) = 2 , x ≠ 2, g2(x) = – 1
x–2 2
g (x) = –
2 1
2
g (
x–2
2
) =–1
2
2 = – 1
2 –2 2
x–2
2 ÷ 2 – 2x + 4 = – 1
x–2 2
2× x – 2 =–1
6 – 2x 2
x–2 =–1
3–x 2
2(x – 2) = –(3 – x)
2x – 4 = –3 + x
x=1
Self Practice 1.6 (Page 16)
1. (a) Given f(x) = x – 3, fg(x) = 2x2 – 4x + 7
fg(x) = 2x2 – 4x + 7
g(x) – 3 = 2x2 – 4x + 7
g(x) = 2x2 – 4x + 10
g: x ˜ 2x2 – 4x + 10
(b) Given f(x) = x2 + 1, fg(x) = x2 + 4x + 5
fg(x) = x2 + 4x + 5
[g(x)] + 1 = x2 + 4x + 5
2
[g(x)]2 = x2 + 4x + 4
[g(x)]2 = (x + 2)2
g(x) = x + 2
g: x ˜ x + 2
2. (a) Given f(x) = x + 1, gf(x) = x2 – 2x – 3
gf(x) = x2 – 2x – 3
g(x + 1) = x2 – 2x – 3
Let y = x + 1
x=y–1
g(y) = (y – 1)2 – 2(y – 1) – 3
= y2 – 2y + 1 – 2y + 2 – 3
= y2 – 4y
Thus, g(x) = x2 – 4x or g: x ˜ x2 – 4x
(b) Given f(x) = x2 + 3, gf(x) = 2x2 + 3
gf(x) = 2x2 + 3
g(x + 3) = 2x2 + 3
2
Let y = x2 + 3
x2 = y – 3
x = !w y–3
13
y – 3)2 + 3
g(y) = 2(!w
= 2(y – 3) + 3
= 2y – 6 + 3
= 2y – 3
Thus, g(x) = 2x – 3 or g : x → 2x – 3
14
Self Practice 1.7 (Page 18)
1. (a) Given f(x) = x , x ≠ –1
x +1
f 2(x) = f [ f(x)] f 3(x) = f [f 2(x)] f 4(x) = f [f 3(x)]
= f x (x+1 ) = f (x
2x + 1 ) = f x
3x + 1( )
= x
x
+ 1 = 2x
x
(
+ 1 ) = 3x
x
+1 ( )
x+1
x +1
(x
2x + 1
+1 ) x
3x + 1( +1 )
= x ÷ x+x+1 = x ÷ x + 2x + 1 = x ÷ x + 3x + 1
x+1 x+1 2x + 1 2x + 1 3x + 1 3x + 1
= x × x+1 = x × 2x + 1 = x × 3x + 1
x + 1 2x + 1 2x + 1 3x + 1 3x + 1 4x + 1
= x ,x≠–1 = x ,x≠–1 = x ,x≠–1
2x + 1 2 3x + 1 3 4x + 1 4
(b) f 20(x) = x , x ≠ – 1
20x + 1 20
f (x) =
23 x , x ≠ – 1
23x + 1 23
1
2. (a) Given f(x) = , x ≠ 0
x
f (x) = f [f(x)]
2
f 3(x) = f [f 2(x)] f 4(x) = f [f 3(x)]
= f(x)
=f 1 ( )
x = 1, x ≠ 0
( )
=f 1
x
1 x 1
= =
( )
1
x ( )
1
x
= x = x
(b) f 40(2) = 2
f 43(2) = 1
2
3. (a) Ar(t) = A[r(t)]
= A 2 t3( )
3
( )
= 4π 2 t3
2
3
( )
= 4π 4 t6
9
= 16 πt6
9
(b) When t = 2,
A(2) = 16 π(2 6)
9
= 113 7 π m2
9
15
4. (a) (i) v(t) = 200 + 100t
(ii) v = πr 2h
h = v 2
πr
(iii) hv(t) = h(200 + 100t)
= 200 + 2100t
πr
Apabila jejari, r = 20 cm,
When radius,
hv(t) = 200 + 100t
π(20) 2
= 2+t
4π
(b) When t = 20,
2 + 20
h(20) =
4π
11
=
2π
= 1.75 cm
5. (a) r(t) = 3 × t
= 3t
(b) Ar(t) is the area of the water ripple, in cm2, as a function of time, t, in seconds.
(c) A = πr2
Ar(t) = A[r(t)]
= π(3t)2
= 9 πt2
When t = 30,
Ar(30) = 9π(30 2)
= 8 100π cm2
16
(b) fg(2) = 2 – 1
2+1
= 1
3
( )
2 – 1 –1
( )
gf – =1 2
2
( )
2 – 1
2
=2
(c) fg = gf
x – 1 = 2x – 1
x+1 2x
2x(x – 1) = (x + 1)(2x – 1)
2x2 – 2x = 2x2 – x + 2x – 1
3x = 1
x= 1
3
2. Given f(x) = x , x ≠ 1, g(x) = hx + k, g(3) = 8, gf(2) = 5
x–1
(a) g(3) = 8
3h + k = 8…1
gf(2) = 5
g(2) = 5
2h + k = 5…2
1 – 2: h = 3
Substitute h = 3 into 1.
3(3) + k = 8
9+k=8
k = –1
Thus, h = 3 and k = –1.
(b) fg(a) = 3
f(3a – 1) = 3
3a – 1 = 3
3a – 1 – 1
3a – 1 = 3
3a – 2
3a – 1 = 9a – 6
6a = 5
a= 5
6
( )
3. Given f(x) = ax – b, g(x) = x + 4, fg(2) = 9, gf 1 = 2
2
fg(2) = 9
f(2 + 4) = 9
f(6) = 9
6a – b = 9…1
( )
gf 1 = 2
2
( )
g 1 a – b = 2
2
17
1a–b+4= 2
2
a – 2b = –4
a = 2b – 4 …2
Substitute 2 into 1.
6(2b – 4) – b = 9
12b – 24 – b = 9
11b = 33
b=3
Substitute b = 3 into 2.
a = 2(3) – 4
=6–4
=2
Thus, a = 2 and b = 3.
4. Given f(x) = 2 , x ≠ 3, g(x) = hx2 + k
x–3
(a) Given g(2) = 5, gf(1) = –1
g(2) = 5
(22)h + k = 5
4h + k = 5…1
gf(1) = –1
g(–1) = –1
h + k = –1…2
1 – 2: 3h = 6
h=2
Substitute h = 2 into 1.
4(2) + k = 5
k=5–8
= –3
Thus, h = 2 and k = –3.
(
(b) gf(x) = g 2
x–3 )
(
=2 2
x–3 ) 2
–3
(
=2 2 4
x – 6x + 9) –3
= 8 – 3x + 18x – 27
2
x – 6x + 9
2
= –3x + 18x 2– 19 , x ≠ 3
2
(x – 3)
5. Given f(x) = ax + b, f 3(x) = 27x + 13
(a) f 2(x) = f(ax + b)
= a(ax + b) + b
= a2x + ab + b
f 3(x) = f [f 2(x)]
= f(a2x + ab + b)
= a(a2x + ab + b) + b
= a3x + a2b + ab + b
18
By comparison,
a3x + a2b + ab + b = 27x + 13
a3 = 27 and a2b + ab + b = 13
a=3 9b + 3b + b = 13
13b = 13
b= 1
Thus, a = 3 and b = 1.
(b) f 4(x) = f [f 3(x)]
= f(27x + 13)
= 3(27x + 13) + 1
= 81x + 39 + 1
= 81x + 40
6. (a) A(x) = x2
V(A) = 10A
(b) VA(x) = V[A(x)]
= 10x2
= 10A
7. Given f(x) = x + 6
(a) fg(x) = 2x2 – 3x – 7
g(x) + 6 = 2x2 – 3x – 7
g(x) = 2x2 – 3x – 13
(b) gf(x) = x2 + 4
g(x + 6) = x2 + 4
Let y = x + 6
x=y–6
g(y) = (y – 6)2 + 4
= y2 – 12y + 36 + 4
= y2 – 12y + 40
Thus, g(x) = x2 – 12x + 40
(c) gf(x) = 8 – x
g(x + 6) = 8 – x
Let y = x + 6
x=y–6
g(y) = 8 – (y – 6)
= 14 – y
Thus, g(x) = 14 – x
8. (a) g : x ˜ x – 1
3
( )
(b) f x – 1 = x2 – 3x + 6
3
Let y = x – 1
3
x = 3y + 1
f(y) = (3y + 1)2 – 3(3y + 1) + 6
= 9y2 + 6y + 1 – 9y – 3 + 6
= 9y2 – 3y + 4
19
Substitute y with x,
f(x) = 9x2 – 3x + 4
Thus, f : x ˜ 9x2 – 3x + 4
9. Given f(x) = px + q, f 3(x) = 8x – 7
(a) f(x) = px + q
f 2(x) = f [f(x)]
= f(px + q)
= p(px + q) + q
= p2x + pq + q
f (x) = f [f 2(x)]
3
= f(p2x + pq + q)
= p(p2x + pq + q) + q
= p3x + p2q + pq + q
By comparison,
p3x + p2q + pq + q = 8x – 7
p2q + pq + q = –7
p = 2 4q + 2q + q = –7
7q = –7
q= –1
(b) f 4(x) = f [f 3(x)]
= f(8x – 7)
= 2(8x – 7) – 1
= 16x – 14 – 1
= 16x – 15
(c) f(x) = 2x – 1
f 2(x) = 4x – 3
f 3(x) = 8x – 7
f 4(x) = 16x – 15
Thus, f n(x) = 2nx + 1 – 2n
10. CN(t) = C(100t – 5t2)
= 15 000 + 8 000(100t – 5t2)
= 15 000 + 800 000t – 40 000t2
Inquiry 3 (Page 20)
3. Yes, the graphs of each function and its inverse are symmetrical about the line h(x) = x, which
is the line y = x.
Self Practice 1.8 (Page 21)
1. (a) f(4) = –5 (b) f –1(–1) = 6 (c) f –1(2) = –2 (d) f –1(–5) = 4
2. Given g(x) = 5 , x ≠ 2 and h(x) = 3x + 6
2– x
(a) g(12) = 5
2 – 12
= – 1
2
20
(b) Let a = g–1(4)
g(a) = 4
5 =4
2–a
5 = 8 – 4a
4a = 3
a= 3
4
Thus, g–1(4) = 3
4
(c) h(–1) = 3(–1) + 6
=3
(d) Let a = h–1(9)
h(a) = 9
3a + 6 = 9
3a = 3
a=1
Thus, h–1(9) = 1
–1 –1
1 l
–2 –2
l l
4 4
2 2
A B B A
(b) h h–1
x x+2
–2 0 0 –2
0 2 2 0
2 4 4 2
4 6 6 4
C D D C
2. g–1 is not a function because there are objects that have two images. h–1 is a function
because each object has only one image.
3. The type of functions that can have an inverse is a one-to-one function.
Inquiry 5 (Page 23)
2. gf(1) = g(1) = 1 gf(3) = g(5) = 3
f(1) = 1 g(1) = 1
fg(1) = f(1) = 1 fg(5) = f(3) = 5
f(2) = 3 g(3) = 2
f(3) = 5 g(5) = 3 gf(2) = g(3) = 2 gf(4) = g(7) = 4
f(4) = 7 g(7) = 4 fg(3) = f(2) = 3 fg(7) = f(4) = 7
21
3. fg(x) = x where x in the domain of g and gf(x) = x where x in the domain of f.
Inquiry 6 (Page 23)
4. Domain
Graph Range
Graph of function f 0<x<8 0 < f(x) < 4
Graph of function g 0<x<4 0 < f(x) < 8
5. If two functions f and g are inverses of each other, then the domain of f = the range of g and
the domain of g = the range of f.
6. The graph of g is the reflection of the graph of f on the line y = x.
Inquiry 7 (Page 24)
4. For any real numbers, a and b, if the point (a, b) is on the graph of f, then the point (b, a) is
on the graph of g, that is the inverse of the graph of f. The point (b, a) on the graph of g is
the reflection of the point (a, b) on the graph of f on the line y = x.
f(x)
4
Horizontal
line test
x
–2 0 2
When the horizontal line test is done, the horizontal line cuts two points on the graph.
This shows that this function is not a one-to-one function and does not have an inverse
function.
22
(g) The graph of function f(x) = 1 , x . 2 is sketched as follows:
(x – 2)2
f(x)
Horizontal
line test
x
0 2
When the horizontal line test is done, the horizontal line cuts only one point on the
graph. This shows that this function is a one-to-one function and has an inverse.
(
=3 x+2 –2
3 ) = 3x – 2 + 2
3
=x =x
Thus, the functions of f and g are inverses of each other.
(b) Given f(x) = 2x , g(x) = 3x
x–3 x–2
fg(x) = f ( x 3x– 2 ) gf(x) = g( x 2x– 3 )
2( 3x ) 3( 2x )
= x–2 = x–3
(x – 2)
3x – 3
(x – 3)
2x – 2
= 6x ÷ 3x – 3x + 6 = 6x ÷ 2x – 2x + 6
x–2 x–2 x–3 x–3
= 6x × x – 2 = 6x × x – 3
x–2 6 x–3 6
= x = x
Thus, the functions of f and g are inverses of each other.
(c) Given f(x) = 2 , g(x) = 3x – 2
x –3 x
(
fg(x) = f 3x – 2
x ) gf(x) = g ( x –2 3 )
= 2 3( 2 ) – 2
(
3x – 2 – 3
) = x–3
x
= 2 ÷ 3x – 2 – 3x
( x –2 3 )
x 6 – 2x + 6 ÷ 2
=
=2× x x–3 x–3
–2
= –x = 12 – 2x × x–3
x–3 2
=6–x
Thus, the functions of f and g are not inverses of each other.
23
(d) Given f(x) = 2 + 5x, g(x) = x – 5
2
(
fg(x) = f x – 5
2 ) gf(x) = g(2 + 5x)
= 2 + 5x – 5
=2+5 x–5
2 ( ) 5x –
2
3
=
= 4 + 5x – 25 2
2
= 5x – 21
2
Thus, the functions of f and g are not inverses of each other.
3. Given f(x) = x3 for the domain –1 < x < 2.
f(x)
8
2
1 f −1
x
−1 0 1 2 8
–1
The domain of the function f –1 is –1 < x < 8 and the range is –1 < f –1(x) < 2.
4. Given h(x) = x2 – 2 for the domain 0 < x < 3.
(a) y
7 h
3 h −1
x
−2 0 3 7
−2
24
(
5. (a) P 1 , –2
2 )
(b) Q(–3, 1)
(c) R(5, 4)
(d) S(–8, –6)
6. (a) y
y = f −1( x ) Bʹ(10, 3)
x
0
Aʹ(2, − 1)
(b) a = 1, b = 4
Self Practice 1.10 (Page 28)
1. (a) Given f(x) = 2x – 5
Let y = 2x – 5
2x = y + 5
y+5
x=
2
Since x = f –1(y),
f –1(y) = x
y+5
=
2
Substitute the variable y with x,
f –1(x) = x + 5
2
Thus, f –1 : x → x + 5
2
(b) Given f(x) = 3 , x ≠ 0
x
Let y = 3
x
x= 3
y
Since x = f –1(y),
f –1(y) = x
= 3
y
Substitute the variable y with x,
f –1(x) = 3
x
Thus, f –1 : x ˜ 3 , x ≠ 0.
x
25
(c) Given f(x) = 4 ,x≠1
x–1
Let y= 4
x–1
x–1= 4
y
4+y
x=
y
Since x = f –1(y),
f –1(y) = x
4+y
=
y
Substitute the variable y with x,
f –1(x) = 4 + x
x
Thus, f : x ˜ + x , x ≠ 0.
–1 4
x
(d) Given f(x) = 5 x ,x≠6
x– 6
Let y = 5x
x–6
y(x – 6) = 5x
xy – 6y = 5x
xy – 5x = 6y
x(y – 5) = 6y
6y
x=
y–5
Since x = f –1(y),
f –1(y) = x
6y
=
y–5
Substitute the variable y with x,
f –1(x) = 6x
x–5
Therefore, f : x → 6x , x ≠ 5.
Thus –1
x–5
(e) Given f(x) = x + 9 , x ≠ 8
x–8
Let y= +9 x
x–8
y(x – 8) = x + 9
xy – 8y = x + 9
xy – x = 8y + 9
x(y – 1) = 8y + 9
8y + 9
x=
y–1
26
Since x = f –1(y),
f –1(y) = x
8y + 9
=
y–1
Substitute the variable y with x,
f –1(x) = 8x + 9
x–1
Thus f : x ˜ 8x + 9 , x ≠ 1.
Maka, –1
x–1
(f) Given f(x) = 2 x – 3,x≠ 1
2x – 1 2
Let y= 2x – 3
2x – 1
y(2x – 1) = 2x – 3
2xy – y = 2x – 3
2xy – 2x = y – 3
x(2y – 2) = y – 3
y–3
x=
2y – 2
Since x = f –1(y),
f –1(y) = x
y–3
=
2y – 2
Substitute the variable y with x,
f –1(x) = x – 3
2x – 2
Thus f –1 : x ˜ x – 3 , x ≠ 1.
Maka,
2x – 2
2. (a) Given f(x) = 3 – x, x ≠ 0
2x
Let y = 3 – x
2x
2xy = 3 – x
2xy + x = 3
x(2y + 1) = 3
3
x=
2y + 1
Since x = f –1(y),
f –1(y) = x
3
=
2y + 1
Substitute the variable y with x,
f –1(x) = 3 , x ≠ – 1
2x + 1 2
Thus, f (4) =
–1 3
2(4) + 1
= 3
9
= 1
3
27
(b) f(x) = f –1(x)
3–x = 3
2x 2x + 1
(3 – x)(2x + 1) = 3(2x)
6x + 3 – 2x2 – x = 6x
2x2 + x – 3 = 0
(2x + 3)(x – 1) = 0
2x + 3 = 0 or x – 1 = 0
x= – 3 or x=1
2
The possible values of x are – 3 and 1.
2
3. Given h(x) = 4x + a and h–1(x) = 2bx + 5
8
h(x) = 4x + a
Let y = 4x + a
4x = y – a
y–a
x=
4
Since x = h –1(y),
h–1(y) = x
y–a
=
4
Substitute the variable y with x,
h–1(x) = x – a
4
Compare with the function h–1,
x – a = 2bx + 5
4 8
x – a = 2bx + 5
4 4 8
1 = 2b and – a = 5
4 4 8
8b = 1 –8a = 20
b= 1 a = – 20
8 8
= – 5
2
4. (a) f (x) = 6x + 7
–1
Let x = 6y + 7
6y = x – 7
y= x–7
6
Thus, f : x ˜ x – 7
6
(b) f –1(x) = 2 – x
5
2–y
Let x = 5
5x = 2 – y
y = 2 – 5x
Thus, f : x ˜ 2 – 5x
28
(c) f –1(x) = 3x , x ≠ 3
x–3
3y
Let x =
y–3
xy – 3x = 3y
y(x – 3) = 3x
y = 3x
x–3
Thus f : x ˜ 3x , x ≠ 3
Maka,
x–3
5. Given g (x) =
–1 4 ,x≠k
2 –x
(a) 2 – x = 0
x=2
Thus, k = 2.
(b) g–1(x) = 4
2–x
Let x = 4
2–y
2x – xy = 4
xy = 2x – 4
y = 2x – 4
x
g(x) = 2x – 4, x ≠ 0
x
( )
2 1 –4
Thus g
Maka, ( )
1 = 2
2
( )
1
2
= –6
Horizontal
line test
This function has an inverse This function has an inverse This function does not have
function because the function because the an inverse function because
horizontal line cuts only one horizontal line cuts only one the horizontal line cuts more
point on the graph. point on the graph. than one point on the graph.
29
3. (a) (b) (c)
y y y
(2, 4) (4, 8)
4
f
f −1 f (8, 4)
(4, 2) 2
f f −1 f −1
x
x 0 2 4 x
0 0
30
5. Given h–1(x) = 2 ,x≠3
3–x
(a) Let x= 2
3–y
3x – xy = 2
xy = 3x – 2
y = 3x – 2
x
Thus, h(x) = 3x – 2_ , x ≠ 0
___
x
(b) h(x) = 2
3x – 2 = 2
x
3x – 2 = 2x
x=2
6. Given f(x) = 4x – 17, g(x) = 5 , x ≠ 31
2x – 7 2
f(x) = 4x – 17 g(x) = 5
Let y = 4x – 17 2x – 7
4x = y + 17 Let =y 5
2x – 7
y + 17
x= 2xy – 7y = 5
4
Since x = f –1(y), 2xy = 5 + 7y
f –1(y) = x 5 + 7y
x=
y + 17 2y
= Since x = g–1(y),
4
x + 17 g–1(y) = x
Thus, f (x) =
–1
5 + 7y
4 =
2y
Thus, g (x) =
–1 5 + 7x
2x
f –1(x) = g–1(x)
x + 17 = 5 + 7x
4 2x
2x(x + 17) = 4(5 + 7x)
2x2 + 34x = 20 + 28x
2x + 6x – 20 = 0
2
x2 + 3x – 10 = 0
(x + 5)(x – 2) = 0
x + 5 = 0 or x–2=0
x=2
7. (a) Given f(x) = 17 (220 – x)
20
Let y = 17 (220 – x)
20
20 y = 220 – x
17
x = 220 – 20 y
17
31
Since x = f –1(y),
f –1(y) = x
= 220 – 20 y
17
Thus f (x) = 220 – 20 x
Maka, –1
17
(b) f(16) = 17 (220 – 16)
20
= 173.4
8. Given V = 4 πr3
3
(a)
V = 4– πr3
r 3
f
f –1
(b) 4 πr3 = 1
3 2
r =
3 1 3
2 4π ( )
= 3
8π
r= 3
!w3
8π
= 0.49 cm
Mastery Practice
1. (a) (i) 1
(ii) 6, 8, 9
(b) Yes, because each object has only one image.
(c) Domain = {2, 6, 7, 8, 9}
Codomain = {1, 4, 5}
Range = {1, 4}
2. (a) (–2)2 – 1 = 3
22 – 1 = 3
42 – 1 = 15
62 – 1 = 35
Thus, m = 35.
(b) h : x ˜ x2 – 1
32
3.
y
Vertical y
line test Horizontal
line test
x
0 x
0
This graph is a function because the vertical line test cuts only one point on the graph but
not a one-to-one function because the horizontal line test cuts more than one point on the
graph.
4 f ( x ) = x − 3
x
−1 0 3 7
x
− 10 3 7
−3
x – 3 = 2x – 3
x – 3 = –(2x – 3) or x – 3 = 2x – 3
3x = 6 x=0
x=2
Thus, x = 2.
Given f(x) = hx + k , x ≠ 0
5. Diberi
x
(a) f(2) = 17
2h + k = 17
2
4h + k = 34
k = 34 – 4h…1
f(3) = 23
33
3h + k = 23
3
9h + k = 69…2
Substitute 1 into 2.
9h + 34 – 4h = 69
5h = 35
h=7
Substitute h = 7 into 1.
k = 34 – 4(7)
= 34 – 28
=6
Thus, h = 7 and k = 6.
(b) f(6) = 7(6) + 6
6
= 43
6. Given f(x) = x + 2 , x ≠ 2, g(x) = mx + c, g–1(2) = f(3), gf –1(2) = 5
x–2
x
f(x) = + 2
x–2
Let y = + 2
Katakan x
x–2
xy – 2y = x + 2
xy – x = 2 + 2y
x(y – 1) = 2 + 2y
2 + 2y
x=
y–1
Thus f (x) = 2 + 2x , x ≠ 1
Maka, –1
x–1
g(x) = mx + c
Katakan y = mx + c
mx = y – c
y–c
x=
m
Thus g (x) = x – c
Maka, –1
m
g (2) = f(3)
–1
2–c = 3+2
m 3–2
2 – c = 5m
5m + c = 2…1
gf –1(2) = 5
g(6) = 5
6m + c = 5…2
2 – 1: m = 3
Substitute m = 3 into 1.
5(3) + c = 2
c = –13
Thus, m = 3 and c = –13.
34
7. (a) (i) f(x) = 3x – 2
Let y = 3x – 2
3x = y + 2
y+2
x=
3
Thus the function that maps set B to set A is f –1(x) = x + 2 .
Therefore,
3
(ii) gf(x) = 6x + 1
g(3x – 2) = 6x + 1
Let y = 3x – 2
3x = y + 2
y+2
x=
3
(
g(y) = 6
y+2
3 ) +1
= 2y + 5
Thus, g(x) = 2x + 5
(b) fg(x) = 4x – 3
f(2x + 5) = 4x – 3
3(2x + 5) – 2 = 4x – 3
6x + 15 – 2 = 4x – 3
2x = –16
x = –8
m
8. Given f(x) = + n, x ≠ k, f(2) = 3, f(3) = 2
x–1
(a) k = 1
(b) f(2) = 3
m +n=3
2–1
m + n = 3…1
f(3) = 2
m +n=2
3–1
m + 2n = 4…2
2 – 1: n = 1
Gantikan n = 1 into
Substitute ke dalam
1. 1.
m+1=3
m=2
Thus, m = 2 and n = 1.
(c) f 2(x) = f [f(x)]
(
= f 2 +1
x–1 )
= 2 +1
2 +1–1
x–1
= 2 +1
( 2
x–1)
= x–1+1
= x
35
(d) f(x) = 2 +1
x–1
Ley y = 2 + 1
x–1
y–1= 2
x–1
x–1= 2
y–1
x= 2 +1
y–1
f –1(x) = 2 + 1, x ≠ 1
x–1
Thus, f –1(2) = 2 + 1
2–1
=3
9. (a) (i) Continuous function
(ii) –4 < f(x) < 4
(b)
y
Horizontal
line test
1
x
–3 0 1
–4
Graph of f does not have an inverse function because the horizontal line test cuts more
than one point on the graph.
10. (a) The functions f(x) = x and f(x) = x4 are one-to-one functions with the condition that the
domain of f is x > 0.
1
(b) f –1(x) = x, f –1(x) = x 4
11. The graph does not necessarily need to intersect at the line y = x if the graph for a function
and its inverse intersect. Both of these graphs might intersect on other lines.
12. Given f(x) = ax + b
cd + d
Let y= ax +b
cd + d
cxy + dy = ax + b
x(cy – a) = b – dy
b – dy
x=
cy – a
f –1(x) = b – dx , x ≠ a
cx – a c 36
(a) (i) f(x) = x + 8 , where a = 1, b = 8, c = 1 and d = –5
x–5
f (x) = 8 + 5x , x ≠ 1
–1
x–1
(ii) f(x) = 2x – 3 , where a = 2, b = –3, c = 1 and d = 4
x+4
f –1(x) = –3 – 4x, x ≠ 2
x–2
(b) f = f –1 if a = –d.
13. (a) (i) (ii)
y=x
3
f –1
2
( 0, 2 )
f
1
( 2, 0 )
–1 0 1 3
–1
The range of f is –1 < f(x) < 3 and the domain of f –1 is –1 < x < 3.
(b) (i) Yes
(ii) Yes. Any point (b, a) on the graph of f –1 is the reflection of point (a, b) on the graph
on the line y = x.
14. (a) p = 100 – 1 x
4
1 x = 100 – p
4
x = 400 – 4p
! x
and C =
dan + 600
25
When x = 400 – 4p,
Apabila
! 400 – 4p
C= + 600
25
! 4(100 – p)
= + 600
25
2! 100 – p
= + 600
25
2! 100 – p
Thus, C = + 600
25
37
(b) When p = 36,
2! 100 – 36
C= + 600
25
= 0.64 + 600
= 600.64
15.
14
4 x 0.5
h(x) = 2π –––
10
12
10
x + 4 0.5
8 g(x) = 2π –––––
10
x 0.5
6 f(x) = 2π –––
10
–5 0 5 10 15
The period of the pendulum, T depends on the length of the pendulum, l. If the length
increases, the period also increases.
38